1984
DOI: 10.1159/000194650
|View full text |Cite
|
Sign up to set email alerts
|

Drug Intake and Plasma Concentrations in Acute Asthma

Abstract: Drug intake and plasma concentrations of theophylline and β-agonists were recorded in 19 patients with acute asthma (peak expiratory flow rate < 50% of predicted normal value and heart rate > 100 beats/min). 10 of the patients arrived at the hospital twice; accordingly 29 cases of acute asthma were studied. The results show that few patients overdosed their medicine before arrival at the hospital. On the contrary, they were often undertreated. This was verified both by plasma concentrations and drug intake rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…The study provides evidence suggesting that if indeed high doses of inhaled salbutamol are taken by asthmatics during the development of an acute attack before attending hospital, salbutamol does not enter the systemic circulation in significantly large quantities. This suggestion concurs with the findings in acute asthmatics of Boe and Ljungholm (1984).…”
Section: Discussionsupporting
confidence: 93%
“…The study provides evidence suggesting that if indeed high doses of inhaled salbutamol are taken by asthmatics during the development of an acute attack before attending hospital, salbutamol does not enter the systemic circulation in significantly large quantities. This suggestion concurs with the findings in acute asthmatics of Boe and Ljungholm (1984).…”
Section: Discussionsupporting
confidence: 93%
“…The regression coefficient between plasma salbutamol before treatment and PEF increase 30 min after treatment was -0.38 (n=17) for the i. v. treated and -0.22 (n=23) for the inhalation group. with an estimated plasma ~2-agonist level (P-terbutaline x 2 + P-salbutamol) of below or above 60 nmoH No significant correlation was found between the reported inhaled 24 h ~2-agonist dose (mg•kg- 1 ) and the change in PEF after inhaled or i. v. salbutamol treatment.…”
Section: Treatment Effects and Relation To Plasma Levelsmentioning
confidence: 87%
“…Some authors have suggested that the excessive use of self-administered sympathomimetic drugs in patients with acute asthma might delay hospital admission, and thus increase the risk of dying from an attack of asthma (19,20]. Other studies have, however, indicated that patients with severe acute asthma are often undertreated (1,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Low theophylline levels alone were felt to be the cause of the emergency visits, despite clear demonstrations of the poor correlation between drug intake and plasma drug concentration in almost 15% of patients. 15 There has been interest in using salivary theophylline levels to attempt to document compliance. 16 However, there appears to be only lim-ited correlation between salivary levels and the blood theophylline level, which is generally accepted as a measuring standard.…”
Section: Underlying Assumptionsmentioning
confidence: 99%